Hambatan Dan Prospek Hukum Penyelenggaraan Jasa Notaris Secara Elektronik Di Indonesia Memasuki Era Society 5.0 - Muhammad Ricky Ilham Chalid (Universitas Indonesia, 2020)
The development of technology, information and communication in the era of society 5.0 makes notaries must be able to keep up with their ability to provide the best legal services, while the best solutions for notaries in facing the challenges of changing times are cyber notary and remote notary, both of which are also not immune from clashes Indonesia law system, but if resolved properly will be the best solution in facing a society 5.0. Another thing that needs to be considered is the reasons for Indonesia not yet implementing it, such as the suitability of the application of remote notary and cyber notary originating from common law into the Indonesian legal system which is civil law and the legal reasons that prevent its application.Keywords: Indonesia Law System, Cyber Notary, and Remote Notary